Chemoradiotherapy for Inoperable Carotid Body Leiomyosarcoma: A Case Report and Review of Literature - Liu, Cheng-Sheng; Tsai, Jia-Ruey; Kao, Yi-Tzu; Lu, Long-Sheng; Chen, Yin-Ju; Burnouf, Thierry; Wang, Peng-Yuan; Chiou, Jeng-Fong; Ting, Lai-Lei (Frontiers in Oncology, 2021)
Leiomyosarcoma originate from the blood vessels are extremely rare tumor and are sometimes misdiagnosed as atherosclerotic chronic occlusive disease or aneurysm. In addition, poor prognosis was observed as compared with leiomyosarcomas of other origin. Surgical intervention remains the main treatment option for these patients but some patients deemed as inoperable owing to limitations of critical anatomical structures. Here, we report one case of leiomyosarcoma arising from the right carotid body and successful tumor control was achieved with concurrent chemoradiotherapy. A 64-year-old male with the initial presentation of pulsatile right neck pain was diagnosed with right carotid body leiomyosarcoma. Surgical resection harbors the risk of injury to carotid body. Therefore, concurrent chemoradiotherapy was initiated one month after diagnosis confirmed. Irradiation was delivered to right carotid body tumor and regional lymphatics with weekly carboplatin. Investigational liquid biopsy to analyze circulating sarcoma cells was performed to measure cellular sensitivity to cytotoxics. Proliferation suppression was observed to many of the classical agents for sarcoma treatment. The disease remained controlled one year after the treatment and there were no evidence of baroreflex failure. Among vascular leiomyosarcomas, arterial leiomyosarcoma are less common and associated with more aggressive behavior and inferior outcomes as compared with venous leiomyosarcomas. Sarcomas have the risk of cancer relapse despite initial curative treatment. Salvage chemotherapy was associated significant toxicities but the response rate was approximately 30%. In the era of precision oncology, circulating sarcoma cells analyzed for putative drug sensitivity profile has potential to provide personalized data and scientific evidence beyond standard treatment. To our best knowledge, this is the first case report of vascular leiomyosarcoma arising from the right carotid body. Further investigation will be necessary for treating inoperable peripheral arterial leiomyosarcomas with concurrent chemoradiotherapy.